The poetic workmanship of Alexander Pope. - Parkin, Rebecca Price (Univ. of Minnesota Press., 1955)
The Poetic Workmanship of Alexander Pope was first published in 1955. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. Through a detailed examination of Alexander Pope's poetic practices, Mrs. Parkin throws light both on the craftsmanship and on the philosophical concepts which governed the creative thought of the poet. She analyzes Pope's use of such literary devices as irony, antithesis, metaphor, narrative, paradox, tension, tonal variation, and the dramatic speaker. She discusses the Pope's work as a whole. The study also provides an evaluation of the influence on Pope's work of the neo-classical concepts of genre and imitation.